American railways - Eason, Charles (Statistical and Social Inquiry Society of Ireland, 1886)
It will be my aim in this paper, first to exhibit a summary view of the railways as a whole; second, to show from an examination of the accounts of some leading lines, the peculiarities of the financial circumstances of American railways; and third, to review the control exercised over rates in the different States of the Union.
Read Tuesday, 23rd February, 1886
Keywords: American railway system; Railway company finance; 314.15